(untitled) (MIST International Journal of Science and Technology, 2025)
Enter Life quality and socio-economic conditions have improved dramatically over the last century due to the advancement and innovation of modern technology and tools, which have evolved from the fruitful research of scientists. It will continue to grow throughout the twenty-first century and beyond and reach every corner of the globe without any ambiguity. Though scientists research and innovate ideas, technology, and tools for enhancing life quality, productivity, social condition, economy, and environment, inappropriate implementation, strategy, and design could drive society and individuals backwards. Its effect is harshly harmful if scientific innovations are abused and executed recklessly. Recently, humans have encountered severe and periodic natural catastrophes, such as intense hot and cold climates, deluges, tsunamis, typhoons, landslides, droughts, wildfires, pandemics, etc., as well as nation- and society-driven detrimental events, such as riots, wars, espionage, and social phobia. It severely affects the mental health and socio-economic conditions of individuals and society due to the damage to infrastructure, shelter, agricultural land, deaths of humans, animals, and livestock, and environmental pollution. These detrimental events are caused by environmental pollution and global warming, which are also triggered by human activities and the abuse of modern innovations and science. This study explores the most influential impacts of contemporary research and innovation in different fields on society and individuals. It will help to understand and reduce the detrimental effects of research and innovation on society, ultimately enhancing social health and progress. MIJST, Vol. 13, June 2025 : 99-107 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.490(99-107)